The Influence of Emotional Intelligence and Individual Characteristics on Police Employee Performance of Deli Tua Police Officers, Indonesia - Ibnu Rizki Sobirin; Awaludin; Waruwu, Khamo (Open Access Indonesia Journal of Social Sciences, 2024)
The problem of this research is that the performance of police officers is still not optimal in dealing with work stress and pressure, handling conflicts well, or communicating effectively within the scope of work and society where the duties and responsibilities faced by police officers are often heavy and full of pressure. If employees cannot manage stress well, they can experience physical and mental fatigue, which can impact their performance in handling daily tasks. This study aimed to determine both simultaneously and partially the influence of emotional intelligence and individual characteristics on the performance of police employees. The method used is quantitative descriptive using secondary data by distributing questionnaires, processed using the SPSS application with multiple linear regression techniques. The findings of this research are that there is an influence between emotional intelligence and individual characteristics on the performance of police employees both in partial and simultaneous terms. The implication of this research is that emotional intelligence helps police employees manage stress better, remain calm under pressure, and face stressful situations without losing self-control. These emotional and personality aspects play a key role in ensuring effective public services and creating positive relationships with the public.